2019
DOI: 10.1038/s41598-018-37900-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Permeation Enhancers on Skin Permeability: In silico screening using Molecular Dynamics simulations

Abstract: Breaching of the skin barrier is essential for delivering active pharmaceutical ingredients (APIs) for pharmaceutical, dermatological and aesthetic applications. Chemical permeation enhancers (CPEs) are molecules that interact with the constituents of skin’s outermost and rate limiting layer stratum corneum (SC), and increase its permeability. Designing and testing of new CPEs is a resource intensive task, thus limiting the rate of discovery of new CPEs. In-silico screening of CPEs in a rigorous skin model cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 51 publications
2
77
0
Order By: Relevance
“…It was shown that the enhancers can be classified as lipid fluidizers or extractors, and the mechanism of their action in each class can be correlated to their molecular properties including octanol–water partition coefficient and solubility parameters . Computational studies have also confirmed molecular mechanisms of enhancers . Such studies with chemical enhancers have led to unique insights into their mechanism of action as well as the design of novel penetration enhancers.…”
Section: Molecular Properties Of the Carboxylic Acids Used To Create mentioning
confidence: 99%
“…It was shown that the enhancers can be classified as lipid fluidizers or extractors, and the mechanism of their action in each class can be correlated to their molecular properties including octanol–water partition coefficient and solubility parameters . Computational studies have also confirmed molecular mechanisms of enhancers . Such studies with chemical enhancers have led to unique insights into their mechanism of action as well as the design of novel penetration enhancers.…”
Section: Molecular Properties Of the Carboxylic Acids Used To Create mentioning
confidence: 99%
“…The stratum corneum is the outermost layer of the epidermis with insoluble transglutaminase-cross-linked proteins and lipids, and is considered to function as a barrier [85,86]. It is highly selective and allows only small lipophilic molecules to pass through [87]. This brings up a new hypothesis: differences may exist in the accessibility to the receptors, depending on the permeability of the chemicals.…”
Section: The Effects Of Essential Oils and Terpenes Through Non-olfacmentioning
confidence: 99%
“…The platform leverages micro-and macro-scale [41] and is capable of in-silico testing [42]. It can emulate the physicochemical properties of human skin, thereby facilitating the study of how constituents of new formulations are transported through its layers [43].…”
Section: In-silico "Test"mentioning
confidence: 99%